Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1097/01.pec.0000161470.19841.50
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Childhood Poisoning in the Sharon Area in Israel

Abstract: In children with an unequivocal choking event while eating even with normal physical and radiographic findings, FBA requires to be excluded by thorough investigations in such instances. Similarly, in toddlers with unexplained persistent cough with refractory parenchymal infiltrates, unrecognized FBA should also be considered. A witnessed choking event is the most important historical information to make an early diagnosis of FBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 17 publications
(18 reference statements)
4
22
1
3
Order By: Relevance
“…Contudo, em nosso estudo, foi verificada maior frequência por medicamentos de ação central, principalmente antidepressivos. Esses eventos ocorrem independentemente da classe socioeconômica, escolaridade das mães, sazonalidade, idade e sexo 10,11,16,17 . Estudos apontam que crianças que se intoxicam apresentam mais chances de pertencerem a famílias de poucos recursos sociais 8,10 .…”
Section: Discussionunclassified
“…Contudo, em nosso estudo, foi verificada maior frequência por medicamentos de ação central, principalmente antidepressivos. Esses eventos ocorrem independentemente da classe socioeconômica, escolaridade das mães, sazonalidade, idade e sexo 10,11,16,17 . Estudos apontam que crianças que se intoxicam apresentam mais chances de pertencerem a famílias de poucos recursos sociais 8,10 .…”
Section: Discussionunclassified
“…As in other regions, the age groups that were most vulnerable to unintentional poisoning by pesticides in Rio de Janeiro State were children and the elderly 3,4,6,27 . In the study period, children below the age of five and older adults died due to the ingestion of rodenticides.…”
Section: Discussionmentioning
confidence: 99%
“…The major risk factor for unintentional poisoning was that the toxic products were easily accessible. The inadequate storage in homes often led to the ingestion of those products 3,8,14,22,23,24,25 . In many instances the product was within the reach of children or was stored in beverage bottles and caused unintentional poisoning among both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…These events occur regardless of socioeconomic class, educational level of mothers, seasonality, age, and sex. 10,11,16,17 Studies have reported that children who are poisoned are more likely to belong to families with few social resources. 8,10 The lack of significant difference between groups with respect to socioeconomic status of families suggests that the magnitude of this variable has no statistical power.…”
Section: Discussionmentioning
confidence: 99%